RANCANG BANGUN SISTEM PENJADWALAN PRODUKSI MENGGUNAKAN ATURAN PRIORITAS PADA PT. UNICHEM CANDI INDONESIA - Akbar, Rizky Jihad; Setiawan, Henry Bambang; Kusumawaty, Weny Indah (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
PT. Unichem Candi Indonesia is manufacturing company that produce chemical materials products. So far, the order that received by PT. Unichem Candi Indonesia was processed only based by order priority that come first without looking the processing time, work time limit, time length to complete the entire order, and waiting time between completed process until the next operation begins. This production method will cause a problem when the numbers of the orders increased because can cause longer production time and causing delay in the production as well as depletion of orders.The production process in PT. Unichem Candi Indonesia needs a right method of production and appropriate solutions in order to minimize the occurring problem Therefore, the application is made that can provide an optimal model of production in order to reach a company target.The efforts to overcome that problem is to provide analysis production queue solutions based by 4 queue methods, that are first come first serve, short processing time, long processing time, and early due date.From this 4 queue methods, the system will choose in accordance with parameters of which desired, and PT. Unichem Candi Indonesia could have an optimal production process.Keywords : Priority Rules, Production Schedulling